The Revealed Structure. Drawing between Construction and Form (diségno, 2026)
The coherence of built architecture often depends on a latent structural design whose essential role can govern architectural outcomes even when not overtly visible. Structural logic is either integrated into the building as a whole or concealed behind finished surfaces. However, this concealed structure often defines space and regulates formal relationships. Instead of viewing structure and form as opposites or as directly corresponding, it is more accurate to understand them as mutually influential, their relationship shaped by specific design choices. Every construction act creates an order, and every form manifests through its underlying structure, highlighting an ongoing interplay between these elements. [read more]